Scientific Consideration in the Concept of Islamic Law in Indonesia : A Study on The Fatwas of Falakiyah Of MUI - Rasyid, Muhammad; Aseri, Akh. Fauzi; Sukarni, Sukarni; Aseri, Muhsin (Al-Daulah: Jurnal Hukum dan Perundangan Islam, 2023)
This study aims to incorporate scientific consideration in the application of falakiyah fatwas of the Indonesian Ulema Council and maps the patterns of the nexus between religion and science in those fatwas. This research involved a library study and a qualitative method. The approaches took into account ushūl fiqh and scientific approaches. With regard to the theoretical fundamentals, this research adheres to cum-doctrinaire introduced by A. Mukti Ali and the theory relating to the nexus between religion and sciences by Ian G. Barbour. The primary data were sourced from six falakiyah fatwas by the Indonesian Ulema Council from 1976-2010. The data were garnered from documentation and analysed with content analysis. The research results show that scientific studies in falakiyah fatwas of the Indonesian Ulema Council play the following three roles: first, scientific studies are to help understand problems that religious knowledge cannot fathom; second, scientific studies along with syar’ī theorem are referred to as a primary consideration in setting a fatwa; third, the scientific studies serve as the basis of amendments in a fatwa. Unfortunately, Scientific studies are not always consistently taken into account in setting falakiyah fatwah of the council, thereby sparking diverging religious patterns intertwining with sciences in falakiyah fatwas, ranging from conflict relations, independence, and dialogues, to integration.